2008
DOI: 10.1016/j.febslet.2008.12.045
|View full text |Cite
|
Sign up to set email alerts
|

Cu,Zn‐superoxide dismutase is necessary for proper function of VDAC in Saccharomyces cerevisiae cells

Abstract: Edited by Vladimir Skulachev Keywords:Copper-and zinc-containing superoxide dismutase Voltage dependent anion selective channel Channel activity Tob55/Sam50 Tom40 Saccharomyces cerevisiae a b s t r a c t Available data suggest that a copper-and zinc-containing dismutase (CuZnSOD) plays a significant role in protecting eukaryotic cells against oxidative modifications which may contribute to cell aging. Here we demonstrated that depletion of CuZnSOD in Saccharomyces cerevisiae cells (Dsod1 cells) affected distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 34 publications
3
15
0
Order By: Relevance
“…5, the protein carbonylation, which was quantitated after derivatization with 2,4-dinitrophenyl hydrazine, was increased in the Δsod1 cells compared with the wild type cells. This finding supports previously published data that demonstrate oxidative stress in Δsod1 S. cerevisiae cells (e.g., Drakulic et al, 2005;Karachitos et al, 2009;O'Brien et al, 2004). However, the Δsod1 cells treated with the reference substances or the studied extracts contain less carbonylated proteins compared with the untreated cells (see also Table 2).…”
Section: 5supporting
confidence: 93%
See 1 more Smart Citation
“…5, the protein carbonylation, which was quantitated after derivatization with 2,4-dinitrophenyl hydrazine, was increased in the Δsod1 cells compared with the wild type cells. This finding supports previously published data that demonstrate oxidative stress in Δsod1 S. cerevisiae cells (e.g., Drakulic et al, 2005;Karachitos et al, 2009;O'Brien et al, 2004). However, the Δsod1 cells treated with the reference substances or the studied extracts contain less carbonylated proteins compared with the untreated cells (see also Table 2).…”
Section: 5supporting
confidence: 93%
“…A more widely distributed copper-and zinc-containing enzyme (CuZnSOD or SOD1) is localized in the cytosol, peroxisomes, lysosomes, and nucleus, as well as the mitochondrial intermembrane space, whereas manganese-containing enzyme (MnSOD or SOD2) is only present in the mitochondrial matrix (O'Brien, Dirmeier, Engle, & Poyton, 2004;Zelko, Mariani, & Folz, 2002). Interestingly, it has been shown that SOD1 is necessary for the proper function of voltage-dependent anion-selective channel (VDAC) (Karachitos et al, 2009), which is regarded as crucial for proper mitochondria function (e.g., Kmita, Stobienia, & Michejda, 1999) and consequently, cell life or death (e.g., Shoshan-Barmatz et al, 2010). Accordingly, it has also been shown that deficient SOD activity may be involved in the etiology of several diseases (e.g., Torsdottir et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in the presence of minocycline the voltage dependence of reconstituted VDAC is weaker although simultaneously the channel is modified to assume lower conductance states that suggests an effect of minocycline on VDAC gating mechanism [39]. Furthermore flickering of VDAC conductance observed in the presence of minocycline might result from VDAC transient blockade/closure [54].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that VDAC behavior in planar phospholipid membranes made of asolectin is voltage dependent and symmetrical [38][39][40], meaning that the channel closes at about the same rate and to about the same extent depending on the applied potential value but regardless its sign. Thus, VDAC reconstituted into planar phospholipid membranes displays 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 Garcia-Martinez EM et al,…”
Section: Minocycline Affects Vdac Conductance and Voltage Dependencementioning
confidence: 99%
“…Artificial phospholipid membranes were formed from soybean asolectin (Avanti Polar Lipids, purified by acetone precipitation before use) suspended at concentration of 25 mg/ml in n-decane, across a circular hole (aperture diameter about 250 μm) in the thin wall of Delrin chamber (Warner Instruments) separating two compartments (cis–trans) filled with unbuffered 1M KCl (31, 34, 35). The pH of KCl solution was 6.9.…”
Section: Methodsmentioning
confidence: 99%